PENGARUH MANAJEMEN LABA, INTENSITAS MODAL DAN UMUR PERUSAHAAN TERHADAP TAX AVOIDANCE (Studi Empiris Perusahaan Subsektor Property dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020) (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to provide empirical evidence of the effect of Earnings Management, Capital Intensity and Company Age on Tax Avoidance. This study uses a quantitative approach and the data used are secondary data. The population in this study are property and real estate sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The method in determining the sample using purposive sampling. Obtained a sample of 14 companies with a period of five years so that the total obtained is 70 sample data. When testing there are extreme values ??so that 17 sample data experience outliers. The method used is multiple linear regression descriptive statistical test, panel data regression model analysis, the selected model selection test is the Random Effect Model, classic assumption test, multiple linear test and hypothesis testing with the help of statistical data processing Eviews version 9. The results of this study show that Earnings Management, Capital Intensity and Company Age simultaneously have a significant effect on Tax Avoidance. Earnings Management has no significant effect on Tax Avoidance. Capital Intensity has a significant effect on Tax Avoidance. Company age has no significant effect on Tax Avoidance.